Unraveling Zinner Syndrome: Insights from a distinct case - João Ferreira Guerra; João Magalhães Pina; Vanessa Andrade; Miguel Brito Lança; Luís Campos Pinheiro (Ukrainian Journal of Nephrology and Dialysis, 2024)
Zinner Syndrome (ZS) is a rare congenital malformation characterized by a triad of unilateral renal agenesis, ipsilateral seminal vesicle cyst, and ejaculatory duct obstruction. Typically discovered incidentally in the second to fourth decades of life, it presents with varied symptoms, including lower urinary tract symptoms, painful ejaculation, hemospermia, perineal pain, and infertility in 45% of cases.This article describes the case of ZS, highlighting the diagnostic and management approaches. Diagnosis relies on imaging techniques: ultrasound for initial assessment, computed tomography (CT) for detailed anatomical information and magnetic resonance imaging (MRI) as the gold standard for its superior soft-tissue contrast. Treatment depends on symptom severity and cyst size, ranging from conservative management for asymptomatic patients to surgical intervention for symptomatic cases. The primary surgical treatment involves the removal of the seminal vesicle cysts, which can effectively relieve symptoms such as pain, urinary discomfort, and ejaculatory dysfunction, thereby significantly enhancing the patient's quality of life. Minimally invasive laparoscopic or robotic surgery is preferred for its reduced morbidity and shorter recovery time. Infertility management includes surgical relief of ejaculatory duct obstruction and assisted reproductive technologies when necessary. Regular follow-up is essential for monitoring recurrences. Future research should focus on long-term outcomes and standardized management protocols to improve patient quality of life.